Knowledge, Attitudes, and Practices on Do-It-Yourself (DIY) Braces among Public Senior High School Students in Manila S.Y. 2019-2020/Erynne Richelle T. Ongchan. - Ongchan, Erynne Richelle T.
INTRODUCTION: It is during the adolescent stage (ages 10-19 years old), that individuals are most concerned about their physical appearance. Dental braces are fixed appliances used in orthodontics which help correct misaligned teeth to improve function, esthetics, and overall dental health. As early as 2015, DIY braces/ fashion braces have emerged in the Philippines. There are several warnings and reports on the dangers of using DIY braces/ fashion braces in various media outlets, but there are still a number of people who avail of them. In order to understand this trend, this research attempts to determine adolescents’ knowledge, attitudes, and practices towards dental braces and DIY braces.